Inovasi Pembelajaran IPA Melalui Model Problem-Solving Terintegrasi LKPD Kontekstual untuk Penguasaan Materi Getaran dan Gelombang - Hehanussa, Ester Iryanti; Sapulete, Heppy; Nirahua, Juliana; Amahoru, Abdul Haji (Pattimura University, 2024)
This study aims to determine the effectiveness of the application of the problem-solving learning model integrated with context-based Learner Worksheet (LKPD) in improving the mastery of vibration and wave concepts in students of class VIII-2 SMP Negeri 7 Maluku Tengah. This study used a one-group pretest-posttest design involving 29 students as samples selected randomly (random sampling). The LKPD used was developed based on a contextual approach that links physical material with real phenomena in the surrounding environment, such as traditional musical instruments and ocean waves. The data collection instruments consisted of an initial test, a final test, and a student engagement observation sheet. The results showed a significant increase in concept mastery, marked by an increase in the average score from 35.33 in the initial test to 78.31 in the final test, with an N-gain value of 0.50 (medium category). In addition to cognitive improvement, students also showed a better ability to solve problems independently through the problem-solving stages. These findings indicate that the integration of the problem-solving model with context-based LKPD is an effective learning innovation to improve learning outcomes and active involvement of students in science learning.